Coerced and forced sexual initiation and its association with negative health outcomes among youth: Results from the Nigeria, Uganda, and Zambia Violence Against Children Surveys. (October 2019) - Nguyen, Kimberly H.; Padilla, Mabel; Villaveces, Andrés; Patel, Pragna; Atuchukwu, Victor; Onotu, Dennis; Apondi, Rose; Aluzimbi, George; Chipimo, Peter; Kancheya, Nzali; Kress, Howard
Abstract: Introduction: Coerced and forced sexual initiation (FSI) can have detrimental effects on children and youth. Understanding health outcomes that are associated with experiences of FSI is important for developing appropriate strategies for prevention and treatment of FSI and its consequences. Methods: The Violence Against Children Surveys were conducted in Nigeria, Uganda, and Zambia in 2014 and 2015. We examined the prevalence of FSI and its consequences (sexual high-risk behaviors, violence experiences, mental health outcomes, and sexually transmitted infections (STI)) associated with FSI among youth aged 13–24 years in three countries in sub-Saharan Africa. Results: Over one in ten youth aged 13–24 years who had ever had sex experienced FSI in Nigeria, Uganda, and Zambia. In multivariable logistic regression, FSI was significantly associated with infrequent condom use (OR = 1.4, 95%CI = 1.1–2.1), recent experiences of sexual violence (OR = 1.6, 95%CI: 1.1–2.3), physical violence (OR = 2.2, 95%CI: 1.6–3.0), and emotional violence (OR = 2.0, 95%CI: 1.3–2.9), moderate/serious mental distress (OR = 1.5, 95%CI: 1.1–2.0), hurting oneself (OR = 2.0, 95%CI: 1.3–3.1), and thoughts of suicide (OR = 1.5, 95%CI: 1.1–2.3), after controlling for demographic characteristics. FSI was not statistically associated with engaging in transactional sex, having multiple sex partners, or having a STI. Conclusion: FSI is associated with infrequent condom use, recent experiences of violence and mental health outcomes among youth in sub-Saharan Africa, which may increase the risk for HIV and other consequences. Developing strategies for prevention is important for reducing the prevalence of FSI and its effects on children and youth.